Assessment of Feeding Practice among Mothers Attending the Immunisation Clinic of UCMS Hospital, Nepal: A Cross-Sectional Study - Gupta, Binod Kumar; Kafle, Raju; Chaudhary, Nagendra (Journal of Universal College of Medical Sciences, 2021)
INTRODUCTION: Practice of exclusive breast feeding has dramatically reduced infant mortality in developing countries due to reduction in diarrhea and infectious diseases. We conducted a study to assess the feeding practices among mothers with children less than 12 months of age attending the immunization clinic of UCMS hospital, Nepal. MATERIAL AND METHODS: A hospital based cross sectional study was carried out in the immunization clinic of Pediatric ward of UCMS, Nepal for a period of four months. Mothers of child of 0-12 months were included in the study. Sample size was 372 which was based on the number of mothers visited Pediatric ward for immunization of their child of age group 0-12 months during the duration of the study. Mothers were interviewed by using a pre-validated structured questionnaire. Data was analyzed by using SPSS version-20 software and presented by descriptive statistics as frequency and percentages. RESULTS: Most of the children were above six months, 56.5% were of 7-12 months of age group. Exclusive breastfeeding was done in 48.4% children for first six months. Maximum population preferred hospital as their mode of delivery. 93.5% mothers opted for hospital as their place of delivery. 23.4% mothers were illiterate. Night feeding was practiced by 96.2% mothers. CONCLUSION: Breast feeding awareness must be spread among mothers by workshops and health education programs.